Rom, Italien. Neue Argumente zu einer Naumachie im Colosseum. Die Arbeiten der Jahre 2017 und 2018 - Beste, Heinz-Jürgen (e-Forschungsberichte des DAI, 2019)
Since the uncovering of the basement of the Colosseum, archeologists, historians and engineers have been engaged in a bitter controversy over whether or not Naumachia was possible in the Colosseum. Preliminary investigations of a project to cover the arena, in which also the DAI Rome is involved, provided new insights into the canal system in the Colosseum, which gave a new impetus to the discussion about the execution of a Naumachia in the Colosseum.